The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.4269/ajtmh.2011.11-0037
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue-Derived Mesenchymal Stem Cells as a New Host Cell in Latent Leishmaniasis

Abstract: Some protozoan infections such as Toxoplasma, Cryptosporidium, and Plasmodium can be transmitted through stem cell transplantations. To our knowledge, so far, there is no study about transmission of Leishmania parasites in stem cell transplantation and interactions between parasites and stem cells in vitro. Therefore, the aim of this study was to investigate the interaction between different species of Leishmania parasites and adipose tissue-derived mesenchymal stem cells (ADMSCs). ADMSCs have been isolated, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 30 publications
0
37
0
2
Order By: Relevance
“…AMSCs for instance can be infected with various types of Leishmania parasites [65]. IFN-␥ and TNF-␣ costimulated human and murine infected BMSCs are able to eliminate the obligate intracellular parasite: type II Toxoplasma gondii, by upregulating IDO or iNOS expression, respectively.…”
Section: Msc and Fungal And Parasitic Infectionsmentioning
confidence: 99%
“…AMSCs for instance can be infected with various types of Leishmania parasites [65]. IFN-␥ and TNF-␣ costimulated human and murine infected BMSCs are able to eliminate the obligate intracellular parasite: type II Toxoplasma gondii, by upregulating IDO or iNOS expression, respectively.…”
Section: Msc and Fungal And Parasitic Infectionsmentioning
confidence: 99%
“…It is noted that MSCs are infected by L . species [Allahverdiyev et al, ]; however, there is no evidence about MSCs immunomodulatory behaviors in L. major ‐infected tissue. Therefore, we intend to assess the effects of the soluble L. major antigens primed MSCs on macrophage immune responses to lipopolysaccharide (LPS) in both cell‐to‐cell contact‐dependent manner and conditioned media (CM) treatment.…”
mentioning
confidence: 99%
“…In a previous study, we have showed an increase in transforming growth factor-alpha (TNF)-a/IL-10 ratio after co-culture of MSCs with macrophages in BALB/c and C57BL/6 mice in response to Leishmania major (L. major) infection, indicating a positive effect in treatment of leishmaniasis [Dameshghi et al, 2015]. It is noted that MSCs are infected by L. species [Allahverdiyev et al, 2011]; however, there is no evidence about MSCs immunomodulatory behaviors in L. major-infected tissue. Therefore, we intend to assess the effects of the soluble L. major antigens primed MSCs on macrophage immune responses to lipopolysaccharide (LPS) in both cell-to-cell contactdependent manner and conditioned media (CM) treatment.…”
mentioning
confidence: 99%
“…In all assays, positive controls containing L. donovani DNA and a negative control without DNA were included; 10 μL reaction mixture were visualized by 2% agarose gel electrophoresis. 24 Our previously experiments showed that the analytical sensitivity of PCR method was 100 parasites in evaluated samples (unpublished results).…”
Section: Methodsmentioning
confidence: 85%
“…The sample was centrifuged at 15,800 + g for 10 minutes, and the pellet was washed with cold 70% ethanol and then dissolved in 20 μL TE buffer 10/0.1 (10 mM Tris·HCl, 0.1 mM EDTA, pH 8.0). 24 Samples for diagnosis by PCR. PCR has been performed for the amplification of Leishmania-specific gene from miniexon sequences by using DNA extracted from previously infected BALB/c PB and MCM samples.…”
Section: Methodsmentioning
confidence: 99%